PENERAPAN METODE SIX SIGMA (DMAIC) PADA UMKM KERUDUNG DI DESA SUKOWATI BUNGAH GRESIK - Sofiyanurriyanti Sofiyanurriyanti; Mahasin Maulana Ahmad (Universitas Teuku Umar, 2019)
Quality Control is very important in efforts to minimize the number of defective products. One of them is in small and medium businesses in the Kerudung Micro Small And Medium Enterprises in Sukowati Bungah Village, Gresik District, Gresik Regency. This Micro Small And Medium Enterprises owned by Ms. Hj difficultiawati. The purpose of this research is to analyze the defects of veil products by using the Six Sigma method namely DMAIC (Define, Measure, Analuze, Improve, Control). The results of this study indicate that the company has a total number of disability veils of 225 units consisting of untidy edge trimming, creased fabric, holes in the veil fabric, less neat screen printing, inappropriate colors. In the process of making this veil there is a value of the damage ratio on goods by calculating the upper control limit (UCL) of 134.9761 and the Lower Control Limit (LCL) of 73.6899 and the average damage to the CL veil of 104.3333 currently at level 1 sigma so that improvements need to be made to achieve level 6 sigma. Using the Pareto diagram tool and for quality improvement improvements were made to the veil disability with SIPOC (Supplier, Input, Process, Output, Customer).